Perancangan Sistem Informasi Penjualan Buku pada PD. Kencana - Maryani Maryani (Bina Nusantara University, 2014)
PD KENCANA is a company engaged in the sale of school administration equipment, office equipment and so forth. One of the processes that exist in PD KENCANA is the sales process. Based on book sales processes currently running on KENCANA PD, there are still some issues, namely duration of the process of making the sales memorandum book, because the manufacturing process is still done by hand writing. The purpose of this research is to design information systems in PD KENCANA book sales and provide reports on sales data of books with ease and on time. Methodology in the development of this system consists of activities which can be grouped into several stages, systems methodologies used in information system design uses the System Development Life Cycle (SDLC). Book Sales Information Systems In this KENCANA PD can assist the administration in managing the sale of books and making reports. In addition, this information system can also easily generate reports on book sales information per month or per year, accurate, precise and relevant, as expected.